2023
DOI: 10.5455/ovj.2023.v13.i7.3
|View full text |Cite
|
Sign up to set email alerts
|

Immunogenicity of a freeze-dried combined vaccine against Rift Valley fever and bovine ephemeral fever in cattle

Abstract: Background: The target of vaccination is to encourage a strong, covering and long-lasting immune response against antigens. For achieving these objectives; effective adjuvant and new vaccine strategies are demanded to make the vaccine sufficiently immunogenic to instigate a powerful immune response Aim: This study was completed for elaboration and evaluation of freeze-dried combined vaccine against both Rift Valley fever (RVF) and Bovine Ephemeral Fever (BEF) viruses using different stabilizers. Methods: T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…Clinical examination of sheep vaccinated with the two different reconstitutions of lyophilized inactivated RVF vaccines reconstitution (1) with saponin and reconstitution (2) with normal saline) showed no observable symptoms of disease or local reactivity at the injection site during the course of the examination. Similarly, [13] observed that inoculated animals did not experience any unfavorable post-vaccinal reactions after receiving the inactivated lyophilized RVF vaccine diluted with saponin and [26] reported that calves vaccinated with lyophilized inactivated RVF vaccine using Carbopol showing no any abnormal local or systemic clinical signs.…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations
“…Clinical examination of sheep vaccinated with the two different reconstitutions of lyophilized inactivated RVF vaccines reconstitution (1) with saponin and reconstitution (2) with normal saline) showed no observable symptoms of disease or local reactivity at the injection site during the course of the examination. Similarly, [13] observed that inoculated animals did not experience any unfavorable post-vaccinal reactions after receiving the inactivated lyophilized RVF vaccine diluted with saponin and [26] reported that calves vaccinated with lyophilized inactivated RVF vaccine using Carbopol showing no any abnormal local or systemic clinical signs.…”
Section: Discussionmentioning
confidence: 91%
“…They found that the immunological response in sheep given two doses of the lyophilized RVF vaccine, stabilized with lactalbumin and sucrose and diluted with saponin, remained within the protective range until the end of the ninth month after vaccination. Also, these results related to the use of saponin as adjuvant where [26] showed that a superior humoral immune response was induced by the produced freeze-dried vaccine containing both BEF and RVF along with carbopol. The results that were obtained seem to coincide with [19], who revealed that saponin-based adjuvants have the advantage of just requiring a little dose to have an adjuvant effect and can alter the cell-mediated immune response as well as improve the production of antibodies, and [46] who reported that Saponin-based adjuvants (SBAs) are promising new adjuvants that stand out as they not only enforce CD4+T cellmediated immunity but also motivate the antibody response.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations